Groundwater Extraction: Implications on Local Water Security of Peri-urban Area of Kathmandu Valley - Sada, Rajesh; Shrestha, Anushiya; Karki, Kanchan; Shukla, Ashutosh (Nepal Journal of Science and Technology, 2013)
The rapid and haphazard urbanization in Kathmandu valley and expansion of built-up area to the peripheral rural landscapes has resulted to formation of peri- urban areas which are now transforming into urban form. This paper examines how the increasing urban water demand has put unprecedented pressure on groundwater sources in the peri-urban areas of Kathmandu valley. Based on the semi-structured interviews with local people, focus group discussions and key informants interviews, the study found that water security at Jhaukhel is closely associated with groundwater and the dependency of local people on it has increased over the years. The implications of the groundwater extraction coupled with sand mining in the area have been manifested in the form of declining groundwater table and drying of traditional water sources. Despite the growing awareness among the local people on the consequences of depleting groundwater table, in absence of strict regulatory mechanism, the exploitation of groundwater has been adding threat to the local eco-hydrology of the area and subjecting the local community to water insecurity. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 121-128 DOI: http://dx.doi.org/10.3126/njst.v14i1.8932